Activation of Akt signaling in prostate induces a TGFβ-mediated restraint on cancer progression and metastasis - Bjerke, G A; Yang, C-S; Frierson, H F; Paschal, B M; Wotton, D (Oncogene, 2014)
Mutations in the PTEN tumor suppressor gene are found in a high proportion of human prostate cancers, and in mice, Pten deletion induces high-grade prostate intraepithelial neoplasia (HGPIN). However, progression from HGPIN to invasive cancer occurs slowly, suggesting that tumorigenesis is subject to restraint. We show that Pten deletion, or constitutive activation of the downstream kinase AKT, activates the transforming growth factor (TGF)β pathway in prostate epithelial cells. TGFβ signaling is known to have a tumor suppressive role in many cancer types, and reduced expression of TGFβ receptors correlates with advanced human prostate cancer. We demonstrate that in combination either with loss of Pten or expression of constitutively active AKT1, inactivation of TGFβ signaling by deletion of the TGF β type II receptor gene relieves a restraint on tumorigenesis. This results in rapid progession to lethal prostate cancer, including metastasis to lymph node and lung. In prostate epithelium, inactivation of TGFβ signaling alone is insufficient to initiate tumorigenesis, but greatly accelerates cancer progression. The activation of TGFβ signaling by Pten loss or AKT activation suggests that the same signaling events that have key roles in tumor initiation also induce the activity of a pathway that restrains disease progression.